A corpus study of verbs in opinion articles of The Jakarta Post and the relation with text characteristics - Ikmi Nur Oktavianti; Asmad Adnan (English Language Teaching Educational Journal, 2020)
As one of the text categories, opinion texts have distinctive characteristics compared to any other texts in newspapers, including the choice of verb usage. This study then aims at preliminarily examining the verbs used in opinion articles in The Jakarta Post to find out the relation between frequency and text characteristics. This study collected the opinion articles of The Jakarta Post comprising 47.143 words. This study was assisted by Lancsbox to store the corpus of opinion section texts, to identify the verb lemmas, and to count the frequency of verbs. The verbs found in this study were then classified based on Scheibman’s main verb classification (which is based on Halliday’s and Dixon’s verb types). The results of the study show that there are three most frequent verb types used in opinion texts in The Jakarta Post; they are material, verbal, and feeling verb types. Meanwhile, the lesser frequent ones are perception, possessive/relational, relational, and cognition verbs types. Meanwhile, the least frequent verb types are existential, corporeal and perception/relational verbs types. As opinion text conveys the argument of the writer, it is plausible to find feeling verb type belongs to the third most frequent types, along with material type to show concrete actions and verbal type to report the information. These frequencies exhibit that there is a firm relationship between text characteristics and the tendency of verb choice.